Biochemical characterization of the Î²-mannanase activity of Bacillus paralicheniformis SVD1 - Clarke, Matthew David (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2019)
Products produced via the enzymatic hydrolysis of lignocellulosic biomass, the most abundant renewable terrestrial source of carbon, can potentially replace a lot of the fuels and chemicals currently produced using non-renewable hydrocarbons. Mannan is a polysaccharide component of lignocellulose that is abundant in softwoods and legume seeds. Enzymatic hydrolysis of mannan by Î²-mannanases has various industrial applications, including use in biofuel and prebiotic mannooligosaccharide (MOS) production for the improvement of human and animal health. The industrial use of Î²-mannanases depends on their biochemical characteristics, such as their activity, stability and substrate specificity. Knowledge of their synergistic interactions with other enzymes is also useful for effective hydrolysis. Bacillus paralicheniformis SVD1 was used as a source for Î²-mannanases. The two mannanases of B. paralicheniformis SVD1 have not been biochemically characterized apart from minor characterization of crude Î²-mannanase activity. The protein sequences of the two Î²-mannanases, of glycosyl hydrolase family 5 and 26, have a 95% - 96% identity to the Î²-mannanases of B. licheniformis DSM13T (=ATCC14580T). These small protein sequence differences could lead to quite different biochemical characteristics. These mannanases were characterized as these enzymes may have industrially useful characteristics. To induce mannanase production, B. paralicheniformis SVD1 was cultured in broth containing the mannan substrate locust bean gum. Various growth curve parameters were measured over 72 h. Mannanase activity was the highest after 48 h of growth - this was the time at which mannanase activity was concentrated, using 3 kDa centrifugal filtration devices, for biochemical characterization of the crude activity. Zymography revealed that the crude concentrated mannanase fraction consisted of at least two mannanases with relative molecular weights (MWs) of 29.6 kDa and 33 kDa. This was smaller than expected "“ based on their theoretical molecular masses. Protease activity, which was detected in the broth, was probably the reason. There were two pH optima, pH 5.0 and pH 7.0, which also indicated the presence of two mannanases. The concentrated mannanase displayed characteristics that were expected of a B. paralicheniformis Î²-mannanase. The temperature optimum was 50Â°C and the activity loss was less than 7% at 50Â°C after 24 h. Substrate specificity assays revealed that there was predominantly mannanase activity present. Thin layer chromatography (TLC) analysis of mannan and MOS hydrolysis showed that mainly M2 and M3 MOS were produced; only MOS with a degree of polymerization of 4 or higher were hydrolyzed. Hydrolysis was minimal on mannoligosaccharides with galactose substituents. Activity and MOS production was the highest on soluble, low branched mannan substrates. The highest activity observed was on konjac glucomannan. Purification of the mannanase activity was then attempted using various methods. Ammonium sulfate precipitation, acetone precipitation, as well as centrifugal filtration device concentration was assessed for concentration of the mannanase activity.Concentration was not very successful due to low activity yields (â‰¤ 20%). Anion exchange chromatography (AEC) and size exclusion chromatography (SEC) was used for purification. AEC gave good activity yield and fold purification, but SDS-PAGE analysis revealed the presence of many different proteins so further purification was necessary. SDS-PAGE analysis showed that there were only a few protein contaminants in the SEC fraction. However, the yield was too low to allow for biochemical characterization. The optimized purification procedure, which partially purified the mannanase activity, used 85% ammonium sulfate precipitation, followed by AEC. The fold purification was high (88.9) and the specific activity was 29.5 U.mg-1. A zymogram of the partially purified mannanase showed a mannanase active band with a MW of 40 - 41 kDa. A serine protease inhibitor, phenylmethylsulfonyl fluoride (PMSF), was added during the purification steps. This indicated that the mannanase/s in the crude concentrate, without PMSF added, was hydrolyzed by serine protease activity. Native PAGE zymograms suggested that at least two different isoforms of mannanases were present. Additional purification would be required to determine the true characteristics of the mannanase/s. The biochemical characteristics of the crude and partially purified mannanases were similar. The pH optima of the partially purified mannanases were different; the pH optima were 6.0 and 9.0. The substrate specificities were similar, except that the partially purified mannanases displayed no cellulase and Î²-D-galactosidase activity, but showed a small amount of Î±-L-arabinase activity. The partially purified mannanase and a Cyamopsis tetragonolobus GH27 Î±-galactosidase synergistically hydrolyzed locust bean gum. The M50G50 combination displayed the highest extent of hydrolysis; after 24 h there was a 1.39 fold increase in reducing sugar release and the degree of synergy (DS) was 4.64. TLC analysis indicated that synergy increased the release of small MOS. These MOS could be useful as prebiotics. The synergy between the partially purified mannanase and the commercial cellulase mixture CellicÂ® CTec2 (Novozymes) on spent coffee grounds (SCG) was also determined. SCG is an abundant industrial waste product that has high mannan content. The SCG was pretreated using NaOH, and the monosaccharide, soluble phenolics and insoluble contents were determined. Glucose and mannose were the dominant monosaccharides in the SCG; the pretreated SCG contained 20.4% (w/w) glucose and 18.5% (w/w) mannose, respectively. The NaOH pretreatment improved mannanase hydrolysis of SCG. It resulted in the opening up and swelling of the SCG particles and removed some of the insoluble solids. The partially purified B. paralicheniformis SVD1 mannanase displayed no detectable activity on SCG, but showed synergy with CTec2, in terms of DS, on untreated and NaOH pretreated SCG. This is the first report of mannanasecellulase synergy on SCG; other studies found that increased hydrolysis was due to additive effects. The results obtained in this study are only an initial assessment of the biochemical properties of B. paralicheniformis SVD1 mannanase activity and its synergy with other enzymes. These results can be used to inform future studies.
Keywords: Mycobacterium avium paratuberculosis; Enzymes -- Biotechnology; Lignocellulose -- Biotechnology